Reciprocal Effects of Social Support in Major Depression Epidemiology - Patten, Scott B (Bentham Open, 2010)
BACKGROUND: The clinical course and epidemiology of major depressive episodes (MDEs) may be influenced by reciprocal interactions between an individual and the social environment. Epidemiological data concerning these interactions may assist with anticipating the clinical needs of depressed patients. METHODS: The data source for this study was a Canadian longitudinal study, the National Population Health Survey (NPHS), which provided 8 years of follow-up data. The NPHS interview included a brief diagnostic indicator for MDE, the Composite International Diagnostic Interview Short Form for Major Depression (CIDI-SFMD). The NPHS interview also incorporated the Medical Outcomes Study Social Support Scale (MOSSS) and a set of relevant demographic and health-related measures. The MOSSS assesses total social support and four specific dimensions of social support. Hazard ratios (HR) were used to quantify associations in the longitudinal data. RESULTS: Lower quartile total social support ratings predicted MDE incidence: the HR adjusted for age and sex was 1.9 (95% CI 1.6 – 2.2). Lower quartile ratings in specific social support dimensions yielded similar HRs. MDE was associated with emergence of lower-quartile affection social support (age and sex adjusted HR 1.3, 95% CI 1.1 – 1.7), but other aspects of social support were not consistently associated with MDE. CONCLUSIONS: Low social support appears to be a robust risk factor for MDE and can be used to identify persons at higher risk of MDE. Evidence that MDE has a negative effect on social support was weaker and was restricted to affection social support.